The Effects of Nateglinide and Octreotide on the Uterus in Rats with Experimentally Developed Polycystic Ovary Syndrome: A Histopathological Study - Deniz, Ömür Gülsüm; Kırıcı, Pınar; Annaç, Ebru; Kaplan, Selçuk (The European Research Journal, 2026)
Objectives: It was aimed to investigate the histopathological effects of Nateglinide (NG) and Octreotide (OC) on uterine morphology in rats with experimentally induced polycystic ovary syndrome (PCOS). Methods: Forty-two female Sprague-Dawley rats (10-12 weeks old, 340-360 g) were divided into six groups (n=7 per group) as Control, PCOS, PCOS+NG, NG only, PCOS+OC, OC only. PCOS was induced via daily oral administration of Letrozole (1 mg/kg) for 21 days. Treatment groups received NG (oral, 30 days) or OC (intraperitoneal, 0.1 mg/kg/day for 30 days). After the experiment, the uterus tissues of all rats were dissected and subjected to histopathological examinations after histological procedures. Results: Histopathological analysis revealed significant uterine damage in the PCOS group compared to other groups (P0.05). Treatment with NG or OC in PCOS rats led to improved epithelial and glandular morphology and reduced Mast cell density, no evidence of edema, and inflammation was found in the connective tissue of these treated groups, suggesting partial improvement of PCOS-induced uterine pathology (P